Hollow man [videorecording (DVD)] - Verhoeven, Paul, 1938-; Shue, Elisabeth; Bacon, Kevin, 1958-; Brolin, Josh (Columbia TriStar Home Video, 2000)
After years of experimentation, Dr. Sebastian Caine, a brilliant but arrogant scientist working for the Defense Department, has successfully transformed mammals to an invisible state and brought them back to their original physical form. Detemined to achieve the ultimate breakthrough, Caine instructs his team to move on to phase III: human experimentation. Dr. Caine uses himself as the first subject.